Homeomorphism between Sphere and Cube - Idris, Amidora; Ahmad, Tahir; Maan, Normah (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2008)
In this paper, we present the construction of homeomorphism from unit sphere; S2 to unit cube; C3. On route, we produced an explicit mapping between the two topological spaces where proving by construction is mainly adopted in this work